Aproveitamento e Caracterização do Lodo de ETE para Fins Energéticos e como Adição Pozolânica para o Concreto - Suarte Junior , Fernando Moreno (Universidade Federal do Tocantins, 2019)
The present work deals with the environmental sanitation of solid waste, focused on the sludge generated at the North Sewage Treatment Plant (ETE-Norte) of Palmas-TO. The responsible concessionaire, BRK Ambiental, performs the collection, treatment and final destination of domestic sewage generated in the capital master plan, being the generating source responsible for seeking the most appropriate method for the final destination of the waste. Sludge is a solid waste generated in large quantities in the treatment of sewage, being a problem in the environmental sanitation the final destination of this waste, since the presence of heavy metals can pollute the soil and water sources. With the objective of minimizing environmental impacts and suggesting a final disposal method with material utilization, the work proposes to verify the physical and chemical characteristics of the sludge, determine its calorific value and verify the pozzolanic reactivity of the ash. The waste generated in the incineration process was considered a pozzolantic addition and included in the concrete composition, being inserted in contents of 5 and 10% in the replacement of the Portland cement in the concrete dosage. The comparative studies of the results of the reference concrete and the concrete with sludge ash contents of the sewage treatment plant presented satisfactory results that make feasible the use of the sludge as an input to the concrete, since the analyzed specimens presented resistance to axial compression near the reference trace and above the determined fck in the dosage. The tensile strength and modulus of elasticity are satisfactory, compared to the standards. Regarding the ash, it was verified that there is a pozzolanic reactivity, verified through the electric conductivity, in the thermal treatment by incineration, the sludge presented high calorific value compared to other residues, making feasible the use of the same as combustible material and making possible the use of the ash in the concrete.